2020
DOI: 10.3390/nu12123679
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition: Percentage and Association with Prognosis in Patients Hospitalized for Coronavirus Disease 2019

Abstract: Previous studies have found a correlation between malnutrition and prognosis in respiratory infections. Our objectives were to determine (i) the percentage of malnutrition, and (ii) its prognosis in patients admitted for coronavirus disease 2019 (COVID-19). In this monocentric retrospective study, we consecutively included all adult patients presenting with acute COVID-19 between 9 April and 29 May 2020. Malnutrition was diagnosed on low body mass index (BMI) and weight loss ≥ 5% in the previous month and/or ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 43 publications
10
73
1
4
Order By: Relevance
“…Three studies used both traditional measures and calculated indices [ 34 , 45 , 55 ]. COVID-19 related outcomes addressed in these studies included disease severity [ 34 ], COVID-19 complications (such as renal/hepatic injury [ 45 ] and muscle dystrophy [ 41 ]), admission to the ICU [ 47 ], need for oxygen therapy [ 56 ], and in-hospital mortality [ 41 , 43 , 45 , 47 , 54 , 55 ]. One study evaluated the length of hospital stay (LOS), hospital expenses, loss of appetite, and weight loss [ 34 ] while many studies evaluated the association between malnutrition and markers of inflammation [ 28 , 41 , 45 , 53 , 54 , 55 ].…”
Section: Measures Used For Nutritional Screening In Covid-19 Patiementioning
confidence: 99%
See 2 more Smart Citations
“…Three studies used both traditional measures and calculated indices [ 34 , 45 , 55 ]. COVID-19 related outcomes addressed in these studies included disease severity [ 34 ], COVID-19 complications (such as renal/hepatic injury [ 45 ] and muscle dystrophy [ 41 ]), admission to the ICU [ 47 ], need for oxygen therapy [ 56 ], and in-hospital mortality [ 41 , 43 , 45 , 47 , 54 , 55 ]. One study evaluated the length of hospital stay (LOS), hospital expenses, loss of appetite, and weight loss [ 34 ] while many studies evaluated the association between malnutrition and markers of inflammation [ 28 , 41 , 45 , 53 , 54 , 55 ].…”
Section: Measures Used For Nutritional Screening In Covid-19 Patiementioning
confidence: 99%
“…Compared with severely ill patients, critically ill patients express significantly lower levels of total protein, serum albumin, and prealbumin as well as significantly higher levels of serum urea nitrogen, creatinine, glucose, and total bilirubin [ 28 , 37 ]. Nutritional markers in severe/critical COVID-19 patients correlated with NRS-2002 [ 28 ] and NRI [ 56 ]. Likewise, among remitting patients, MNA scores correlated with nutritional markers [ 52 ].…”
Section: Measures Used For Nutritional Screening In Covid-19 Patiementioning
confidence: 99%
See 1 more Smart Citation
“…Until 12 December 2020, we have identified three peer‐reviewed publications investigating the occurrence of weight loss before, during, or after hospital treatment of in total 589 COVID‐19 patients (Table 1). One study 10 was performed at the time of hospital admission and reported on weight loss ≥5% before the index hospitalization, one study 11 investigated weight loss ≥5% until the examination date during hospitalization, and one study 6 assessed weight loss of patients in remission (i.e. after hospitalization).…”
Section: Cachexia Diagnosis and Frequency During Covid‐19mentioning
confidence: 99%
“…Subjects who had a ≥10% weight loss showed a significant association with decreased eating function and transition to parenteral feeding. Allard et al [ 23 ] reported that a large number of patients admitted due to COVID-19 had malnutrition. COVID-19 is also known to cause gastrointestinal symptoms, diarrhea, mild abdominal pain, nausea, vomiting, and loss of appetite, making it a potential cause of nutritional disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%